Right-wing extremism in contemporary Germany - Braunthal, Gerard 1923-2014 (New perspectives in German political studies, 2009)
"This study of the German right-extremist movement looks at the three rightist political parties, neo-Nazi groups, skinhead gangs, and New Right intellectuals. It poses the question whether, at a time of global recession, the existing democratic system is resilient enough to meet the challenges posed by the xenophobic and racist groups"--Provided by publisher